Jmjd1c demethylates STAT3 to restrain plasma cell differentiation and rheumatoid arthritis - Yin, Yuye; Yang, Xinyi; Wu, Shusheng; Ding, Xinyu; Zhu, Huamin; Long, Xuehui; Wang, Yuliang; Zhai, Sulan; Chen, Yun; Che, Nan; Chen, Jingjing; Wang, Xiaoming (Nature immunology, 2022)
Appropriate regulation of B cell differentiation into plasma cells is essential for humoral immunity while preventing antibody-mediated autoimmunity; however, the underlying mechanisms, especially those with pathological consequences, remain unclear. Here, we found that the expression of Jmjd1c, a member of JmjC domain histone demethylase, in B cells but not in other immune cells, protected mice from rheumatoid arthritis (RA). In humans with RA, JMJD1C expression levels in B cells were negatively associated with plasma cell frequency and disease severity. Mechanistically, Jmjd1c demethylated STAT3, rather than histone substrate, to restrain plasma cell differentiation. STAT3 Lys140 hypermethylation caused by Jmjd1c deletion inhibited the interaction with phosphatase Ptpn6 and resulted in abnormally sustained STAT3 phosphorylation and activity, which in turn promoted plasma cell generation. Germinal center B cells devoid of Jmjd1c also acquired strikingly increased propensity to differentiate into plasma cells. STAT3 Lys140Arg point mutation completely abrogated the effect caused by Jmjd1c loss. Mice with Jmjd1c overexpression in B cells exhibited opposite phenotypes to Jmjd1c-deficient mice. Overall, our study revealed Jmjd1c as a critical regulator of plasma cell differentiation and RA and also highlighted the importance of demethylation modification for STAT3 in B cells. The STAT3 pathway is activated in B cells by interleukin-6 and interleukin-21; however, methylation of Lys140 prevents its dephosphorylation and deactivation. Yin et al. report a noncanonical role for the histone demethylase Jmjd1c in demethylating phosphorylated STAT3, thereby terminating B cell activation and limiting plasma cell generation and potential B cell-mediated autoimmunity.